Association between sexuality and quality of life in older adults - Edison Vitório de Souza Júnior; Diego Pires Cruz; Cristiane dos Santos Silva; Randson Souza Rosa; Gabriele da Silva Santos; Namie Okino Sawada (SciELO, 2021)
ABSTRACT Objective: To analyze the association between the experiences of sexuality and quality of life in older adults. Method: Cross-sectional study developed with a total of 300 older adults living in northeastern Brazil. Data collection was carried out entirely online between August and October 2020. Participants completed the online questionnaire containing three instruments for assessing bio sociodemographic data, sexuality and quality of life. Data analysis was performed using the Mann-Whitney, Kruskal-Wallis, Spearman correlation and multivariate linear regression tests, adopting a 95% confidence interval (p < 0.05). Results: Older adults experience better affective relationships and have better quality of life in sensory abilities and intimacy. In the regression analysis, only affective relationships (β = 0.510; [95% CI: 0.340-0.682]; p < 0.001) and physical and social adversities (β = −0.180; [95% CI:−1.443-0.434]; p < 0.001) remained associated with the general quality of life of older adults. Conclusion: Health professionals must invest in training, development of individual and group educational interventions, in addition to promoting the strengthening of bonds between older adults so that they feel free and comfort in expressing their intimate needs.